Psychological Resilience as a Putative Mediator Between Psychological Distress and Quality of Life in Drug-Resistant Tuberculosis: A Gap-Mapping Scoping Review - Sri Arini Winarti Rinawati; Sarka Ade Susana; Nur Hidayat (Borneo Scientific Publishing, 2026)
Drug-resistant tuberculosis (DR-TB) is a prolonged and burdensome condition often associated with psychological distress and reduced quality of life (QoL). Although resilience is considered a protective factor in chronic illness, its role in linking distress and QoL in DR-TB remains unclear. This review aimed to map whether psychological resilience has been directly operationalized as a mechanism linking psychological distress to QoL in DR-TB, and to identify evidence gaps for future longitudinal mediation research. A gap-mapping scoping review guided by the framework and reported using PRISMA 2020 was conducted. PubMed/MEDLINE was searched directly; equivalent Boolean strings were also prepared for Scopus and Web of Science for institutional verification. Hand-searching and citation chaining were performed across major indexed journal platforms for studies published from January 2021 to May 2026. Eligible empirical records addressed active TB or DR-TB and reported at least two constructs relevant to the target pathway (psychological distress, QoL, resilience, coping, social support, self-efficacy, self-management, stigma, or mediation-type relationships). Included studies were charted by design, population, DR-TB specificity, temporal ordering, mediation/path testing, resilience operationalization, and key relevance. Forty studies from 16 countries/settings were included, all systematically screened against predefined eligibility criteria across title/abstract and full-text stages. Most used cross-sectional designs, with fewer longitudinal, qualitative, mixed-methods, or intervention studies. No study directly examined psychological resilience as a mediator between psychological distress and QoL in DR-TB. However, evidence suggested that distress, stigma, adverse drug reactions, and socioeconomic hardship were linked to poorer QoL, while social support, adaptive coping, self-management, self-efficacy, family care, and routinisation were associated with better psychosocial outcomes. The recent evidence base strongly supports a psychosocial pathway connecting distress to poorer QoL in TB and likely in DR-TB, but direct mediation testing of resilience in DR-TB remains absent. The field is ready for longitudinal DR-TB studies that measure resilience explicitly, collect repeated distress and QoL outcomes, and test causal mediation instead of treating resilience only as a narrative or inferred construct.